A comparative analysis of the perceptions on the interior design process among interior design students from two selected higher education institutions - Perdido, Francelyn Joy F.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
This study compared the perceptions of the interior design process among interior design students from two selected higher education institutions offering undergraduate interior design programs. The study determined whether there was a common knowledge of the interior design process among the school, identified the various interior design processes used by fourth year interior design students from selected higher education institutions, investigated how interior design process is implemented by the students and analyzed the similarities and differences among these institutions interior design processes. The study employed a descriptive research approach which involved collection of quantitative and qualitative information. Participants were selected using purposive sampling. Interior design students were selected based on the following criteria: the interior design students must be in their fourth year level, and must have experienced several individual interior design projects in the academe. Forty-two (42) interior design students responded to the online survey questionnaire and twelve (12) interior design students participated in the in-depth interview. The study revealed that majority of the fourth year interior design students from both schools have been introduced to the design process and were also able to clearly define the design process. The study likewise revealed that interior design students developed their own design processes and others followed or relied on the design process taught to them by their design educators. It also appeared that interior design students had used different methods, techniques and tools when working on their design projects. Furthermore, majority of the interior design students utilized Internet throughout the process. Some interior design students get design ideas from photos on Pinterest, and some went online to search for interior design journals or research articles, and other downloadable documents. In this study, the researcher likewise has developed an understanding on the true definition of research and how important it is to utilize valuable research articles or journals in the research phase. Hence, the researcher suggests that it is also imperative for interior design students from both schools to also consider using interior design journals or research articles to keep them updated with the latest materials or technologies and likewise to generate better design solutions in their design projects. This is to ensure that as they practice interior design in the future, health, safety and welfare of the users or clients would be prioritized, and more importantly, these sources would keep them updated with the interior design.
Submitted June 2016.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Interior design students -- Philippines